The Right to be Forgotten as Protection for Children Victims of Non-Consensual Pornography Crime - Renald Markus Sinaga; Manunggal Kusuma Wardaya (Faculty of Law, Universitas Jenderal Soedirman, 2021)
Revenge porn refers to the distribution of sexually explicit images without the consent of the pictured individual, in most cases, this happens when someone decides to end the relationship with their partner, the partner who refused their decision then threatens to spread their sexually explicit images on the internet. So far, the existing legal system only accommodates aspects of criminal prosecution for non-consensual pornography offenders. However, if we conduct further observation, the protection that is most needed by the victims is how to reduce the negative impact of this which can harm their future. The right to forget is a right that gives a person the right to delete their data from search engines and other directories under certain circumstances. In a general context, this right is still problematic to adopt because it can threaten the rights for freedom of speech. However, in the context above, this right may be important to be applied for the protection of someone against mistakes made under the age of age. Convention on the Rights of the Child articles 16 & 40 (2) (b) (vii) as explained by the children's rights committee in General comment no. 10 (2007) on Children's rights in juvenile justice in the “Full respect of privacy” section guarantees the rights of child perpetrators of criminal offenses to be kept secret, even in the Beijing rules article 21.1 & 21.2 regulate to avoid stigmatization and/or prejudice or to increase penalties then the record of child offenders is not may be used in subsequent cases when the child is an adult.Keywords: child porn; human rights; nonconsensual pornography; porn revenge; right to be forgotten